Analysis Of the Impact in Phoneme Pronunciation Disorder and Lexicon Mastery Towards Autistic Children - Kesi, Kesi; Subyantoro, Subyantoro; Naryatmojo, Deby Luriawati (Universitas Negeri Semarang, 2021)
The autistic children have limitations in their linguistic development. Those limitations caused by the disorder of phoneme pronunciation and lexicon mastery towards the children. This disorder can have the impact in communication. This research aims to describe the form of phoneme pronunciation disorder and lexicon mastery towards autistic children in Autisma Yogasmara Special School and Griya Shada Semarang as the dorm for children in special needs. This is qualitative research with descriptive method. The data collection technique used in this research note are recording, observing, and taking note techniques. The source of this research is obtained from direct recording of the conversation between the autistic children and their therapist. The analysis method used in this research is direct element review with these several ways: 1) transcribing the data that has been obtained, 2) observing and taking note to the data card, 3) classifying and analyzing data, 4) summing up the result of the analysis. The result of the research shows that autistic children in Autisma Yogasmara Special School and Griya Shada Semarang have communication disorder as the effect from the disorder of phoneme pronunciation and lexicon mastery. The form of communication disorder in autistic children is echolalia which is the effect from disorder of phoneme pronunciation, one way communication, and difficulty in saying one word is the effect from low lexicon mastery.